Internet – pierwsze źródło (dez)informacji - Smołucha, Danuta (Perspektywy Kultury, 2020)
The Internet is the first medium in which controlling the content has become difficult or even impossible. One of its reasons is the fact that the Internet users – who so far were only passive recipients of media messages – have gained the possibility to create and distribute their own messages. Thus, they have become active participants of the participatory culture, in which it is difficult to distinguish between professional and amateur content. The boundaries between private and public domains have become blurred. The distribution of forces shaping public opinion has changed, because the content comes from large media corporations and nonprofessional creators alike.The Internet message is characterized by instantaneous distribution, the ease of editing and modifying its content, and vagueness of authorship. These features make the Internet particularly susceptible to disinformation purposefully aimed at manipulating its users. The fact that every activity undertaken by the Internet users is recorded and analysed is also conducive to manipulation attempts, as the data obtained this way are used to shape their opinions and influence their decisions.The aim of the article is to undertake a discourse on information and disinformation on the Internet in the context of the development of new digital communication tools. The article provides the examples of information manipulation, which could happen only in such an interactive and multimedia medium as the Internet.